Determinants of underweight among HIV-Infected children in pastoral communities of Southern Ethiopia: a facility-based cross-sectional study - Tagese Yakob; Awoke Abraham; Abraham Bezabih; Mesfin Manza Jaldo; Begidu Yakob; Eskinder Israel (BMC Public Health, 2025)
Abstract Background The effect of HIV infection on the nutritional status of patients has been widely known for several years, as well as the synergy between the infection and the conditions of poverty in developing countries. However, particular communities like pastoralists in underdeveloped countries live in a unique crossroad where challenges related to HIV prevention and control, and vulnerability to the disease exacerbate each other. Thus information from such range of contexts is valuable in addressing the complicated medical condition resulting from the combination of HIV infection and malnutrition. This study therefore aimed to assess the nutritional status and its associated factors among HIV infected children from pastoral zones of south Ethiopia. Methods Multicenter cross-sectional study was conducted among 399 HIV-positive ≤ 15 year children. Data were collected systematically from selected participants by using interviewer administered structured and pre-tested questionnaires. We used Epi-data version 4.1 for data entry and SPSS Version 25for data analysis. A p-value of < 0.05 was considered to declare statistical significance with the corresponding 95% confidence interval. The goodness of fit (GOF) of the model was checked using Hosmer-Lemeshow test. The p-value of the Hosmer-Lemeshow test of this model is p-value greater than 0.05 which confirms that the model is correctly specified. Results The magnitude of underweight (weight-for-age z-score ≤ -2) was found to be 50.1%, 95% CI (0.45–0.55).In the multi-variable analysis, the mothers ‘age of15 to 18 years(AOR = 2.02; 95% CI = 1.10–3.71), mother’s exposure to mass media(AOR = 1.58; 95% CI = 1.05–2.39), household food insecurity(AOR = 1.92; 95% CI = 1.18–3.13) and having history of Oropharyngeal disease(AOR = 1.56; 95% CI = 1.01–2.39) were significantly associated with being underweight. Conclusion The prevalence found in this study was high when compared with the local studies. Policies and intervention strategies aimed at improving childhood nutrition and health should address the identified determinant factors.